The midwife’s role in lactation care in Poland - Surówka, Jadwiga; Humaj-Grysztar, Magdalena; Madetko, Renata (Nursing Problems / Problemy Pielęgniarstwa, 2021)
Breast milk is perfectly adapted to the individual nutritional needs of the child. The World Health Organization recommends exclusive natural feeding of infants until they reach 6 months of age. Midwives provide women with lactation support before and after childbirth. Their care continues after discharge from hospital during home visits. Nowadays, most women experience breastfeeding difficulties, indicating the importance of the midwife’s role in lactation care. The role of midwives in antenatal care is to provide information on the physiology of lactation and to present the benefits of breastfeeding for the mother and child. An important element of antenatal education is the initial preparation of the pregnant woman for breastfeeding. The role of midwives after delivery is to ensure skin-to-skin contact of the newborn and its mother. They teach the correct way to latch the baby onto the breast and help to choose a proper position for feeding. The community midwife takes care of the women after discharge from hospital. They visit the mother and the baby in their home environment. During home visits, the midwife assesses the newborn’s and the mother’s health, the newborn’s physical development and weight gain, and provides lactation support. The midwife’s lactation advice is based on the following: medical interview, observation of the mother’s general and mental condition, breast examination, suckling assessment, and evaluation of the breastfeeding efficiency. The midwife provides lactation advice, taking into account the anatomical conditions in the structure of the mother’s breast and the child’s oral cavity.